Contemporary Clinical Research in the Management of Pelvic Organ Prolapse in the United States: A Systematic Review. Issue 11 (24th November 2022) - Sandozi, Arshia; Kaplan-Marans, Elie; Polland, Allison
Abstract : Importance: Pelvic organ prolapse (POP) can cause bothersome symptoms that negatively affect quality of life. Management strategies include observation, conservative management, and surgery. Objective: The purpose of this study was to evaluate the current focus of research in POP. Study Design: We queried clinicaltrials.gov, a registry of clinical research studies maintained by the U.S. National Library of Medicine, for active, recruiting, and enrolling studies involving POP. Results: A total of 104 unique clinical trials were included for analysis. Investigators most commonly specialized in obstetrics and gynecology (obstetrician-gynecologists [ob-gyns]; n = 66, 57.9%); urologists numbered 5 (4.4%). The most common subspecialty was urogynecology (n = 46, 40.4%). Seventy-six percent of clinical research involved surgical intervention. The second most common field of research was diagnostic evaluation of POP (8.4%). Only 12.1% of clinical research focused on conservative measures, and 2.8% investigated medications. Objective outcome measures were used more often than subjective or mixed measures (42.3%, 22.3%, and 32.7%, respectively). The most common outcome measure was Pelvic Organ Prolapse Quantification (14.5%), followed by the mixed measure, "composite success" (8.7%). Conclusions: Urologists are less involved in POP research than ob-gyns. Urogynecologists from either background are most involved. Most clinical research involves surgical management of POP, despite the fact that less than 20% of women pursue surgical correction. Despite dubious concordance with quality of life, objective outcome measures are used more often than subjective or mixed measures to assess severity of POP. Clinical research in POP should be directed to better align with the needs and preferences of patients.